2008
DOI: 10.1128/aem.02480-07
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Diversity of Sequences of Cyanophage Photosynthetic Gene psbA in Marine and Freshwaters

Abstract: Many cyanophage isolates which infect the marine cyanobacteria Synechococcus spp. and Prochlorococcus spp. contain a gene homologous to psbA, which codes for the D1 protein involved in photosynthesis. In the present study, cyanophage psbA gene fragments were readily amplified from freshwater and marine samples, confirming their widespread occurrence in aquatic communities. Phylogenetic analyses demonstrated that sequences from freshwaters have an evolutionary history that is distinct from that of their marine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 31 publications
7
85
0
1
Order By: Relevance
“…For example, bacteriophage structural proteins g20 (portal vertex protein) (Short and Suttle 2005;Sullivan et al, 2008) and gp23 (major capsid protein) (Filee et al, 2005;Jamindar et al, 2012) have been used to identify the diversity and distribution of cyanomyoviruses and T4-like phages. Functional genes like DNA polymerase A (Labonté et al, 2009;Huang et al, 2010) and photosystem genes psbA and psbD (Bench et al, 2007;Chenard and Suttle 2008) have been used as proxies of T7-like podoviruses and cyanophage diversity, respectively. These marker genes, which have been examined in both cultivated phages and environmental amplicon sequence data, have yielded key insights into the diversity and distribution of their respective phage targets.…”
Section: Discussionmentioning
confidence: 99%
“…For example, bacteriophage structural proteins g20 (portal vertex protein) (Short and Suttle 2005;Sullivan et al, 2008) and gp23 (major capsid protein) (Filee et al, 2005;Jamindar et al, 2012) have been used to identify the diversity and distribution of cyanomyoviruses and T4-like phages. Functional genes like DNA polymerase A (Labonté et al, 2009;Huang et al, 2010) and photosystem genes psbA and psbD (Bench et al, 2007;Chenard and Suttle 2008) have been used as proxies of T7-like podoviruses and cyanophage diversity, respectively. These marker genes, which have been examined in both cultivated phages and environmental amplicon sequence data, have yielded key insights into the diversity and distribution of their respective phage targets.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, have identified compositional variation among locations. In these cases, the patterns appear to be related to salinity, whereby freshwaters harbor cyanophage taxa not found in marine habitats (Short & Suttle 2005, Chénard & Suttle 2008, Sullivan et al 2008, Wang et al 2010. Indeed, we know of only 1 study that found evidence for genetically distinct cyanophage communities across relatively small (<100 km) scales within a marine system (Frederickson et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Patterns over horizontal space are less consistent, however. Some studies suggest that cyanophage composition exhibits little horizontal spatial variation, given that nearly identical cyanophage gene sequences have been identified in surface marine samples collected from distant locations (Zhong et al 2002, Breitbart et al 2004, Short & Suttle 2005, Chénard & Suttle 2008. Other studies, however, have identified compositional variation among locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ocean, the cyanobacteria Synechococcus and Prochlorococcus are the major phytoplankton fixing carbons via photosynthesis (Waterbury et al, 1986;Partensky et al, 1999;DeLong and Karl, 2005;Jardillier et al, 2010), and marine cyanophages reportedly participate in the process by carrying the ratelimiting photosystem II protein D1 in their genomes (Sullivan et al, 2006). Because cyanophage D1 protein were reportedly detectable in other freshwater lakes (Chenard and Suttle, 2008), we tried homology search and also detected D1 proteins in our metaviromes. However, any homology search is highly database-dependent.…”
Section: Viral Community In Ftrmentioning
confidence: 99%